Proses Penciptaan Tari Bintan Harat - Alyana, Melli (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The Binian Harat dance work is inspired by the struggle of a woman (Nyai Balau) who dares to fight criminals (Asang) who come from the upper reaches of the Barito River in Central Kalimantan. The Binian Harat dance work is in the form of a group with five female dancers and Melli Alyana as a dancer and choreographer. The process of creating a dance work consists of ideas or concepts, themes, titles, sources of movement, dancers, floor patterns, properties, make-up and costumes, lighting, stage design, and dance music accompaniment. The process of creating a Binian Harat dance work goes through various processes, one of which is the process of exploration, formation, and evaluation. The choreographer tries to explore, form, then evaluate from the ideas that have been obtained from exploring information about folklore in an area into a dance work. This dance work is based on folklore in Central Kalimantan by strengthening the theme of feminism taken from the story of a woman named Nyai Balau. In this writing, the aim is to achieve results, that the basis of a story can be developed into a dance work by applying aspects in the process of its development in a sequential manner.